HDAC inhibitor SB939 potentiates TRAIL-induced apoptosis in colorectal cancer cells: CRC cells effect of TRAIL-HDAC inhibitor combination - Shin, Min Woo; Seo, Seung Young; Kim, Se Lim; Kim, Sang-Wook (Cellular and Molecular Biology, 2023)
Colorectal cancer (CRC) displays noticeable resistance to chemotherapeutic drugs or innovative tumor cell apoptosis-inducing agents such as tumor necrosis factor-related apoptosis-inducing ligand (TRAIL). Thus, sensitizers are needed to enhance the effects of TRAIL-based cancer therapies. Elevated tumor cell death has been reported when various HDAC inhibitors are administered with TRAIL in various human cancers; however, SB939-TRAIL combined treatment has not been reported. In this study, we determined the ability of SB939 and TRAIL, as single agents or in combination, to inhibit the growth and survival of colorectal cancer cells. Our results demonstrated the effects of SB939 and TRAIL on cell viability, apoptosis, and morphological changes in HT-29 cells. SB939 treatment induces hyper-acetylation of histones and death receptors (DR) by activating MAPK proteins in a dose- and time-dependent manner. The ability of SB939 to sensitize HT-29 cells suggests that SB939 can induce essential changes in cell signaling pathways. Thus, the pan-HDAC inhibitor SB939 sensitizes TRAIL-induced apoptosis via up-regulation of DR5, and SB939-TRAIL combined treatment may target the MAPK pathways and serve as an effective therapeutic strategy against CRC.